Detection of Granulocyte Chemotactic Protein 2 in Serum of Periodontitis Patients - Hussien, Saja GH.; Ali, Basima Gh. (Journal of Baghdad College of Dentistry, 2016)
Background: Chronic periodontitis defined as “an infectious inflammatory disease within supporting tissues of the teeth, progressive attachment loss and bone loss". Aggressive periodontitis is rare which in most cases manifest themselves clinically during youth. It characterized by rapid rate of disease progression .Pro-inflammatory chemokines organized inflammatory responses. Granulocyte chemotactic protein 2 is involved in neutrophil gathering and movement. The purpose of the study is to detect serum of Granulocyte Chemotactic Protein 2 and correlate to periodontal condition in patients with chronic periodontitis, Aggressive periodontitis and Healthy Control subjects and measurement the count of neutrophils for the studied groups.Subjects and methods: Eighty four male and female were enrolled in this study .They were divided into three groups (18) patients with Aggressive periodontitis with age range (20-45) years, (33) chronic periodontitis patients and (33) Healthy control with an age range (30-50). Clinical periodontal parameters were recorded for each group. The concentration of granulocyte chemotactic protein- 2 in serum was quantified by a high-sensitivity enzyme linked immunosorbent assay. Blood neutrophils count were detect for five subjects from each group using light microscopeResult: ANOVA analysis revealed high significant differences in Granulocyte chemotactic protein 2 means between aggressive, chronic and controls. Neutrophils count in aggressive periodontitis is higher than chronic and controls .No significant difference in neutrophils count between aggressive and chronic periodontitis, while significant difference when correlate them with controlsConclusion The concentration of granulocyte chemotactic protein 2 increased with the increase in severity of periodontitis. Higher neutrophils count was found in aggressive periodontitis than chronic and controls. As higher granulocyte chemotactic protein 2 that chemoattract more neutrophils recruitment to the site of inflammation